Analysis of the factors influencing adoption of 3D design digital technologies in Colombian firms. Issue 2 (29th April 2021) - Henao Ram-rez, Ana María; López-Zapata, Esteban
Abstract : Purpose: The purpose of this study is to analyse the factors influencing intention to adopt 3D design digital technologies (3DDTs) by Colombian firms. Design/methodology/approach: A conceptual framework was developed using technology-organization-environment (TOE) and technology acceptance model (TAM) theoretical frameworks. From a sample of 138 firms, a structural equation model was analysed with partial least squares (SEM-PLS). Findings: The study identified that perceived usefulness in the technological dimension; technological competence and top management support in the organizational dimension; and competitive pressures in the environmental dimension, are variables affecting intention to adopt 3DDT. The effects of the mediating variables with respect to intention to adopt the technology are also analysed, such as perceived usefulness on the effect of ease of use; top management support on the effect of technological competence and financial readiness; and competitive pressures on the effect of stakeholder pressure. The model explained 71.1% of the 3DDT intention to adopt. Practical implications: The model can be used as a guideline to ensure a positive outcome of the 3DDT adoption in organizations. The results could be useful to understand a technological adoption process for digital transformation. Originality/value: The proposed model integrates some contributions from the TAM and TOE theories and identifies some novel mediating effects that improve its predictive and explanatory power. Furthermore, this is a pioneering study in empirical research on 3DDT in the context of a developing country, specifically in Colombia. The findings from this study provide a foundation for other studies, as well as constructive insights for digital transformation, due to its infancy in an emerging economy.